Prostat Kanseri Hastalarında Hastalık Evrelerine Göre Anksiyete, Depresyon, Cinsel İşlev Bozukluğu Ve Yaşam Kalitesi - (:unkn) unknown (My University, 2013)
Amaç: Erkeklerde sık görülen prostat kanserinde yaşam kalitesi, ruhsal sorunlar ve cinsel işlev bozukluğu birçok çalışmada incelenmiştir. Ancak hastalığın evrelerine göre etkilerinin incelendiği çalışma sayısı oldukça azdır. Biz bu çalışmada prostat kanserli hastaları evrelerine göre sınıflandırarak yaşam kalitesi, cinsel işlev bozukluğu, anksiyete ve depresyon düzeylerini karşılaştırmayı amaçladık. Yöntem: Üroloji kliniğine başvuran 80 prostat kanserli hasta çalışmaya dahil edildi. Hastalar evrelerine göre lokalize/organa sınırlı, lokal yayılımlı ve metastatik olmak üzere üç gruba ayrıldı. Hastalara kısa form 36 (KF-36), hastane anksiyete depresyon ölçeği (HAD) ve Arizona cinsel yaşantılar ölçeği (ACYÖ) uygulandı. Bulgular: Prostat kanseri evresine göre yaşam kalitesinin fiziksel işlevsellik alt boyutu metastatik prostat kanserli hastalarda organa sınırlı hastalara göre anlamlı derecede düşük bulundu (F=4.53, p=0.014). Prostat kanseri evresi ile anksiyete ve depresyon puanları arasında anlamlı ilişki tespit edilmedi. Organa sınırlı hastalığı olanlarda cinsel istek metastatik hastalara göre daha iyi düzeydeydi (F=5.32, p=0.007). Sonuç: Prostat kanseri olan hastalar, hastalığın çeşitli evrelerinde farklı düzeylerde fiziksel işlevsellik ve cinsel isteksizlik sorunları yaşamaktadırlar. Hastaların takibinde klinisyenler bu iki konuyu göz önünde bulundurmalıdır.

Background: Prostate cancer is common in men and in many studies quality of life, mental health problems and sexual dysfunction were examined in this population. However, there are relatively few studies examining the impact of the disease according to the stages. In this study we aimed to compare the levels of anxiety, depression, quality of life and sexual dysfunction of the prostate cancer patients according to their stages. Method: 80 patients with prostate cancer who applied to urology outpatient clinic were enrolled to the study. Patients were divided into three groups according to their stages; localized/organ-confined, local spread and metastatic spread. Short Form 36 (SF-36), Hospital Anxiety and Depression Scale (HAD) and the Arizona Sexual Experience Scale (ASEX) were performed. Results: According to the stage of prostate cancer, physical functioning subscale of quality of life was significantly lower in patients with metastatic prostate cancer than in patients with organ-confined prostate cancer (F= 4.53, p= 0.014). There were no associations between anxiety and depression scores and the stage of prostate cancer. Sexual desire was better in organ-confined prostate cancer patients compared to metastatic prostate cancer patients (F= 5.32, p= 0.007). Conclusion: The patients with prostate cancer might have different levels of physical functioning and sexual aversion problems at different stages of the disease. The clinicians should consider these two issues during follow-up of these patients.
Anxiety, depression, sexual dysfunction and quality of life in prostate cancer based on stage of the disease
Keywords: Onkoloji; Psikiyatri; Üroloji ve Nefroloji